Оптимальное управление потреблением электроэнергии на основе использования АСКУЭ - Розновец, О. И.; Волощук, Л. А. (НТУ "ХПИ", 2011)
Рассматривается проблема автоматизации учета потребления электроэнергии. Предложена структура АСКУЭ на основе применения технологий построения распределенных информационных систем с базами данных. Описана внедренная на предприятиях г. Одессы и области АСКУЭ «SmartLink».

In given article the problem of automation of the electric power consumption account is considered. The structure of automated system of the commercial account of the electric power on the basis of technologies of construction of the distributed information systems with databases is offered. Introduced on a number of the Odessa region enterprises the automated system of the commercial account of the electric power "SmartLink" is described.
Keywords: учет электроэнергии; база данных; распределенная система; electric power account; database; distributed system